Comparing Different Algorithms for Estimating parameters and Reliability Function of Weibull distribution - Reem Razzaq Abdul Hussein (Iraqi Journal for Administrative Sciences, 2024)
Today computational techniques play an important role in various fields. In this research was to use the language of Matlab programming to simulate and compare three different algorithms are used to estimate the parameter (α,β) and reliability function of two parameters weibulldistribution.the estimation algorithms are moment estimators , maximumlikeihoodestimatorsand L_moment estimators algorithms which implemented on different sample n.and each algorithms is repeated (R=1000),and the results of estimation for parameters and reliability function are compared using statistical measure mean square error and all result are explained in tables.